Legal Consequences of Execution of Land on Which There is a Building of Another Person Based on a Review of the Mortgage Rights Provisions - Karyose, Hans; Suparno, Suparno (Green Publisher Indonesia, 2024)
This study discusses the legal consequences of executing land on which there are buildings owned by other parties, with a focus on the provisions of mortgage rights in Indonesian law. This study explores how land that is mortgaged by the building owner can give rise to complex legal implications, including the issue of priority of rights and protection for building owners who do not have land rights. Moreover, it identifies the obstacles faced in implementing land execution, such as conflicts between land owners and building owners and the lack of clear regulations regarding this situation. This study also suggests efforts that can be made to overcome these problems, such as negotiation and mediation, to reach a fair agreement between the parties involved. Through an in-depth analysis of the related legal issues, this study aims to provide a better understanding of the challenges and solutions in implementing mortgage rights amidst diverse interests.